2002
DOI: 10.1006/viro.2001.1255
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytotoxic T Lymphocyte Responses to Live Attenuated 17D Yellow Fever Vaccine: Identification of HLA-B35-Restricted CTL Epitopes on Nonstructural Proteins NS1, NS2b, NS3, and the Structural Protein E

Abstract: Yellow fever virus (YFV) is a re-emerging problem despite the existence of an effective live-attenuated vaccine. The induction of YFV-neutralizing antibodies undoubtedly contributes to vaccine efficacy, but T lymphocyte responses to YFV likely play a role in long-term efficacy. We studied the T lymphocyte responses to YFV in four vaccinees. Proliferation and cytolytic responses to YFV were demonstrated in all subjects. We isolated 13 YFV-specific CD8(+) CTL lines that recognized epitopes on the E, NS1, NS2b, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 56 publications
4
80
0
2
Order By: Relevance
“…The results presented herein suggest that E is the most immunogenic WNV protein (Fig. 2) and reactivity to two peptides from E (E [17][18][19][20][21][22][23][24][25][26] and E 430 -438 ) dominated the CD8 ϩ T cell response in 40% of our cohort (Fig. 7).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The results presented herein suggest that E is the most immunogenic WNV protein (Fig. 2) and reactivity to two peptides from E (E [17][18][19][20][21][22][23][24][25][26] and E 430 -438 ) dominated the CD8 ϩ T cell response in 40% of our cohort (Fig. 7).…”
Section: Discussionmentioning
confidence: 75%
“…Likewise, a study of four volunteers immunized with the yellow fever virus vaccine demonstrated CTL reactivity against E, NS1, NS2A, NS2B, and NS3 (25). Thus, it is clear that the CD8 ϩ T cell response following flavivirus infection targets against both structural and non-structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We generated HLA/peptide tetramers for the three SNV epitopes presented by HLA-B*3501, and a negative control tetramer using an epitope in the yellow fever virus (YFV) NS1 protein that is presented by HLA-B*3501 (28). The specificity of each tetramer was confirmed by flow cytometry using SNV-and YFV-specific CD8 ϩ CTL lines, and by staining PBMC from an HLA-B3501 ϩ individual with no known exposure to either SNV or YFV (Fig.…”
Section: Quantitation Of Snv-specific Cd8 ϩ T Cells In Pbmc Samplesmentioning
confidence: 99%
“…Co et al [8] identified specific cytotoxic T cells against epitopes on non-structural proteins NS1, NS2b, NS3 and structural protein E of the 17D vaccine virus, which are induced early at day 14 post-vaccination and maintained for 18 months.…”
Section: Introductionmentioning
confidence: 99%